2018
DOI: 10.1080/00140139.2018.1493151
|View full text |Cite
|
Sign up to set email alerts
|

The impact of alerting designs on air traffic controller’s eye movement patterns and situation awareness

Abstract: APW: area proximity warning; ASRS: aviation safety reporting system; ATC: air traffic control; ATCO: air traffic controller; ATM: air traffic management; COOPANS: cooperation between air navigation service providers; HCI: human-computer interaction; IAA: irish aviation authority; MSAW: minimum safe altitude warning; MTCD: medium-term conflict detection; SA: situation awareness; STCA: short term conflict alert; TP: trajectory prediction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…In this paper, the authors attempt to address some of the limitations found in mathematical models of the human pilot by using eye tracking data to provide insight into the way the pilot uses the available information. Although numerous studies have been carried out using eye-tracking for various purposes in aviation, for example recognising scan patterns of a remote air traffic control by a single controller [10], flight deck design [11], augmented reality (AR) in Primary Flight Display (PFD) [9], air traffic controller's situation awareness [7] and understanding human behaviour during aircraft-pilot coupling events [8], there has been limited transfer of this knowledge into the mathematical formulation of pilot behaviour. In this study the authors synchronise temporal and spatial eye-tracking data with aircraft data to study scenarios where the pilot is given an urgent safety critical task.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, the authors attempt to address some of the limitations found in mathematical models of the human pilot by using eye tracking data to provide insight into the way the pilot uses the available information. Although numerous studies have been carried out using eye-tracking for various purposes in aviation, for example recognising scan patterns of a remote air traffic control by a single controller [10], flight deck design [11], augmented reality (AR) in Primary Flight Display (PFD) [9], air traffic controller's situation awareness [7] and understanding human behaviour during aircraft-pilot coupling events [8], there has been limited transfer of this knowledge into the mathematical formulation of pilot behaviour. In this study the authors synchronise temporal and spatial eye-tracking data with aircraft data to study scenarios where the pilot is given an urgent safety critical task.…”
Section: Introductionmentioning
confidence: 99%
“…The number of blinks also reduced considerably with the increasing workload in both tasks. Pupil size is a reliable measure of workload (Beatty, 1982, Mandrick et al, 2016 as it dilates with increasing workload (Batmaz and Ozturk, 2008, Kosch et al, 2018, Truschzinski et al, 2018, Bernhardt et al, 2019, Kearney et al, 2019, Marinescu et al, 2018, Wanyan et al, 2014. Recarte et al, 2008 show that blink inhibition happens in higher workload conditions and so, the blink rate is inversely correlated with the attentional levels and workload experienced by the operator (Veltman and Gaillard, 1996, Brookings et al, 1996, Wilson, 2002, Borghini et al, 2014, Widyanti et al, 2017, Wanyan et al, 2018.…”
Section: Discussionmentioning
confidence: 99%
“…gether with electroencephalogram (EEG) [89], and a study of alerting designs to reduce ATCO response time to alerts [39]. Other applications include eye tracking for input to ATCO support tools [63] and for attention guidance [64].…”
Section: Sensing the Operator With Eye Trackingmentioning
confidence: 99%